Do minimum wages increase job satisfaction? Micro data evidence from the new German minimum wage - Mario Bossler; Sandra Broszeit (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
On 1 January 2015 a new statutory minimum wage of exteuro 8.50 per hour of work was introduced in Germany. Using a difference-in-differences approach, we estimate effects on worker-level outcomes of continuing employees. The results reveal a meaningful absolute increase in the affected workers' pay satisfaction. The increase in job satisfaction is modest and predominantly driven by changes in pay satisfaction implying only a small effect on all other dimensions of job satisfaction. Moreover, effects from the minimum wage on work engagement and turnover intention are virtually zero. – – In Deutschland wurde am 1. Januar 2015 der gesetzliche Mindestlohn von exteuro 8.50 pro Arbeitsstunde eingeführt. Mit einer Analyse von Differenzen-in-Differenzen schätzen wir den Effekt auf Outcomes von anhaltend Beschäftigten. Die Ergebnisse zeigen einen deutlichen absoluten Anstieg in der Entlohnungszufriedenheit von betroffenen Personen. Änderungen in der generellen Jobzufriedenheit sind weitestgehend durch den Anstieg in der Entlohnungszufriedenheit getrieben, sodass nur ein kleiner Effekt auf andere Dimensionen der Jobzufriedenheit bestehen bleibt. Effekte des Mindestlohns auf den Arbeitseinsatz und die Bleibebereitschaft zeigen sich nicht.
Keywords: J28; J38; J63; 330; minimum wage; job satisfaction; work engagement; turnover intention; Germany